Students’ Perception on Using Indonesian Subtitle on English Language Movie to Enhance English Vocabulary - Afrilia, Nur Tasya; Wahid, Abdul; Asfah, Indrawaty; Sudding, Muhammad Fahri Jaya; Susanto, Ashabul Kahfi (Journal of Excellence in English Language Education, 2024)
This study aimed to discover the students’ motivations, students’ perceptions, and students’ strategies of the inclusion of Indonesian subtitles in English language movie as a tool for improving English vocabulary and to find out the challenges in the inclusion of Indonesian subtitles on English language movies in enhancing students' new vocabulary. This research uses a qualitative research design with a descriptive approach to describe the research subject. Data collection techniques using interview. The results of this study discover that student perceived that using Indonesian subtitles while watching English language movies emerges as a significant tool for enhancing students' English vocabulary. But some student also contends that, using Indonesian subtitles while watching English language movies as a tool for vocabulary enhancement presents challenges and limitation that impact its effectiveness as a vocabulary enhancement tool.